Comment on “Taxonomy and the DNA Barcoding Enterprise” by Ebach (2011) - Stevens, Mark I.; Porco, David; D’haese, Cyrille A.; Deharveng, Louis (Zootaxa, 2011)
Since Linnæus (1735) proposed a now globally adopted classification scheme, taxonomists have benefited greatly from the ‘Linnæan Binomial Enterprise’. Ebach’s (2011) concerns, particularly that taxonomy “is slowly dying off”, were around well before DNA barcoding began. Here we discuss the integrative potential of DNA barcoding with morphology, which contrary to Ebach’s comments, has proved a useful addition to the taxonomists tool-kit; such molecular applications to taxonomy are not new and have been widely used by taxonomists for over 30 years (e.g., Kitchener et al. 1984).